Um estudo sobre a composição do construto bem-estar no trabalho - Mota, Patrícia Elaine Santana (2014)
The dynamism of modern life brought complexity and emphasis on work, along with the concern for well-being. There are several approaches to that construct, either by subjective, cognitive, social or labor perspective. Well-being at work describes the relationship between an individual and his work. Several authors have proposed structures for it, with theoretical models, dimensions and empirical evidence. However, any model was not empirically tested or it was composed of the variables such as job satisfaction (JS), job involvement (JI) and Affective Commitment to the Organization (ACO). This dissertation aimed to empirically test this theoretical model for well-being at work (WBW) composed of ACO, JS and JI from two studies. In the first, aiming at analyzing the dimensionality of the scales of each variable, exploratory factor analyses were performed by the analysis of the principal components. The sample consisted of 259 workers who responded in person and virtually to the following instruments: Affective Organizational Commitment Scale (AOCS), Job Satisfaction Scale (JSS), Job Involvement Scale (JIS) and an occupational questionnaire. The results showed that AOCS and JIS remained one-dimensional, with 5 items each scale. The JSS presented four factors, bringing 15 items in total. It was noted a significant relationship between ACO and the type of company, because the ones allocated in the private sector is more affectively committed than whoever is in public sector employment. There was also a significant association between ACO and the number of employees of the company, the fewer employees a company has, the greater the ACO. Moreover, there was a significant relationship between JS and wage increase, so that those who had an increase feel more satisfied than those who did not. The JI was related to salary increase, those who received no raise are more involved with work than those who received. The second study consisted of 206 respondents, also workers and those responded to the online questionnaire as well. When evaluating the factor structure found in Study 1 for each scale by confirmatory factor analysis, we obtained ratification of the data. However, the AOCS and JIS remained one-dimensional with 4 items each one. The JSS, after several adjustments recommended in the analysis, gathered 12 items distributed in 4 factors. In addition, a structural equation modeling was carried out to verify if the variables presented by the theoretical model of WBW is confirmed empirically in the explanatory model of WBW. The adjustment indexes indicated the existence of WBW, remaining the model with 20 items distributed unevenly in three variables. Therefore, the data show that when the employee is satisfied with the job, he feels more involved with it, shows affectively committed to the organization and tends to present well-being at work. It is thereby suggested the development of more studies on specific populations of workers in order to corroborate the influence of these variables on the constitution of the construct and, in addition, examine correlations between the WBW and other constructs.